THERMAL CYCLING AS A METHOD FOR DISINTEGRATION OF BIFIDOBACTERIUM BIFIDUM - Knysh, O.V.; Pakhomov, O.V.; Pogorila, M.S.; Savinova, O.M.; Balak, O.K. (World of Medicine and Biology, 2020)
The study compares the damaging effects of two thermal cycling methods on Bifidobacterium bifidum probiotic strain. The suspensions of freshly isolated bifidobacteria and of bacteria stored under hypothermic conditions for 24 hours were subject to the two methods of tenfold thermal cycling that involved slow cooling to (-23 ± 1) °С or rapid cooling to (-196 ± 1) °С followed by thawing at 37 °С. Cell survival was assessed by means of colony forming units (CFU) counting and by flow cytometry using carboxyfluorescein diacetate (cFDA) as fluorochrome. Thermal cycling with slow cooling to (-23 ± 1) °С had a more pronounced disintegrating effect on bifidobacteria. Preliminary storage of bifidobacteria under hypothermic conditions did not significantly increase their resistance to the disintegrating effect of thermal cycling.
Keywords: bifidobacteria; thermal cycling; survival; flow cytometry; disintegration